We Walk : Life with Severe Autism - Lutz, Amy S. F., 1970- (Book collections on Project MUSE., 2020)
"We Walk combines personal narrative, interviews, and research to examine social issues like inclusion, religion, therapeutics, and friendship through the lens of severe autism"--